SEGMENTASI DAN POSITIONING PERGURUAN TINGGI SWASTA DI SURABAYA - HARIYANTO, CRIESTIANA (Kajian Ilmiah Mahasiswa Manajemen, 2012)
This paper aims to determine the implementation of segmentation and positioning of private university. With the increase in the quality of education means that human resources will be born the better the quality and Indonesia will be able to bring the nation to compete fairly in all areas in the world. Currently interest to college to continue their studies or strata level two is increasing. This is caused by the demands of a career in the company or the motivation of the students to improve themselves through education competencies. To achieve an optimal marketing results, the college must first perform market segmentation, having mapped out the next phase of the market is positioning. Position or image formed by a college has a dominant role in influencing public attitudes toward college.